2021
DOI: 10.2147/ceor.s312523
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Domiciliary High Flow Nasal Cannula Treatment in COPD Patients with Chronic Respiratory Failure

Abstract: Purpose To evaluate the cost-effectiveness of long-term domiciliary high flow nasal cannula (HFNC) treatment in COPD patients with chronic respiratory failure. Patients and Methods A cohort of 200 COPD patients were equally randomized into usual care ± HFNC and followed for 12 months. The outcome of the analysis was the incremental cost per quality-adjusted life-year (QALY) gained, and the analysis was conducted from a healthcare sector perspective. Data on the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…The methods of the Danish clinical trial and the characteristics of the patients have been reported in detail. 14 , 15 Briefly, 200 patients were randomized into usual care ± NHF. At inclusion, acute exacerbations of COPD and hospital admissions one year before inclusion, modified Medical Research Council (mMRC) score, St George’s Respiratory Questionnaire (SGRQ), forced expiratory volume in 1 second (FEV1), 6-minute walk test (6MWT) and arterial carbon dioxide (PaCO 2 ) were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methods of the Danish clinical trial and the characteristics of the patients have been reported in detail. 14 , 15 Briefly, 200 patients were randomized into usual care ± NHF. At inclusion, acute exacerbations of COPD and hospital admissions one year before inclusion, modified Medical Research Council (mMRC) score, St George’s Respiratory Questionnaire (SGRQ), forced expiratory volume in 1 second (FEV1), 6-minute walk test (6MWT) and arterial carbon dioxide (PaCO 2 ) were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Published analysis of the clinical study showed a substantial reduction in exacerbations, as counted via patient diaries and phone calls. 14 , 15 However, the available information does not clarify how non-admitted patients were managed, and detailed information about the timing of these exacerbations is not available. Therefore, in order to avoid double counting and the need to impute missing data, we excluded all patient-reported information from the current analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations